Techniques to screen sorghums for resistance to insect pests - Sharma, H.C.; Taneja, S.L.; Leuschner, K.; Nwanze, K.F. (Andhra Pradesh (India), 1992)
Sumarios (Es, En, Fr)
Ilus.; 27 ref.
Keywords: SORGOS; CEREALES; HORTALIZAS; PLANTAS PARASITAS; INSECTOS DAÑINOS; CONTROL DE PLAGAS